The Role of Social Factors in Building Social Resilience of Former Drug Users in Surakarta City, Central Java - Putro, Henriyadi Wasono; Sholahuddin, Agus; Wahyudi, Catur (Journal of Management World, 2025)
This study explores the challenges and solutions in the social reintegration of former drug convicts in Surakarta City, a region marked by a high prevalence of drug circulation. Key issues include social stigma, economic barriers, and insufficient structured social support. The research focuses on two primary objectives: (1) understanding the role of social actors, families, government, private sector, and civil society organizations (CSOs) in fostering the social resilience of former convicts, and (2) identifying obstacles and supporting factors in the social environment, including strategies to address stigma and economic limitations. Using a qualitative approach, this study involved in-depth interviews and observations of nine primary informants, including family members, close friends, religious leaders, youth leaders, and former convicts, along with supporting informants from the National Narcotics Agency (BNN) of Surakarta, CSOs, and correctional institutions. Thematic analysis revealed that emotional support from families forms the foundation for rebuilding the confidence of former convicts. Government programs, including rehabilitation and skills training, help reduce stigma and improve access to employment. The private sector contributes through Corporate Social Responsibility (CSR) initiatives, providing inclusive job opportunities, while CSOs deliver counseling and community-based empowerment. This research introduces a novel contribution by integrating social role theory, social support theory, and social change theory to analyze the social resilience of former convicts. The findings emphasize that a holistic and collaborative approach involving families, communities, and institutional actors is crucial in overcoming stigma and economic barriers while fostering sustainable social reintegration.